Efeitos do alopurinol em rins isquemicos de caes anestesiados com pentobarbital sodico - Módolo, Norma Sueli Pinheiro [UNESP]; Castiglia, Yara Marcondes Machado [UNESP]; Ganem, Eliana Marisa [UNESP]; Braz, José Reinaldo Cerqueira [UNESP]; Vianna, Pedro Thadeu Galvão [UNESP] (My University, 2000)
Background and Objectives - Allopurinol is a drug which inhibits the formation of noxious renal free radicals. The aim of this study was to evaluate the protecting renal effects of allopurinol in ischemic kidneys of dogs. Methods - Sixteen dogs were anesthetized with sodium pentobarbital and submitted to extracellular volume expansion (1.4 ml.kg-1.min-1), to mechanic ventilation with air, to right nephrectomy and to left renal artery clamping. Changes which might occur in renal morphology and function after 30 min of total ischemia and posterior reperfusion were studied in Group 1 (G1), in addition to the action of allopurinol (50 mg.kg-1) on those kidneys, when administered 24 h before the experiment and 1 h before the ischemic procedure in Group 2 (G2). The following parameters: heart rate, inferior vena cava pressure, mean blood pressure, PAH clearance (PAH(c)), renal blood flow (RBF), renal vascular resistance (RVR), creatinine clearance (Cr(c)), filtration fraction, urine output, plasma and urine osmolality, osmolar clearance, free water, sodium and potassium clearance, urine and fractional sodium and potassium excretion, hematocrit, rectal temperature, and left kidney histology were evaluated in four moments: M1 control, and M2, M3, M4 obtained immediately, 15 and 30 min after unclamping of the left renal artery. In G2, M1, M2, M3 and M4 were obtained 45, 90, 105, and 120 min after the second allopurinol dose. Results - Both groups showed the highest values for PAH(c), RBF, and Cr(c), and the lowest values for RVR in M1. Animals were tachycardiac since the beginning of the experiment both in G1 and in G2. The other parameters were not changed. Left kidney histological evaluation showed alterations compatible with acute tubular necrosis in both experimental groups. Conclusions - Alterations found in renal hemodynamics were compatible with the release of vasoconstrictor substances due to renal ischemia. Allopurinol was not effective in preventing renal alterations caused by ischemia and reperfusion.
Effects of allopurinol in ischemic kidneys of dogs anesthetized with sodium pentobarbital
Keywords: ANIMAL: dog; COMPLICATIONS: renal ischemia; DRUGS: allopurinol; HYPNOTICS, Barbiturate: pentobarbital; allopurinol; creatinine; pentobarbital; potassium; sodium; anesthesia; animal experiment; artery clamp; controlled study; dog; drug effect; female; hematocrit; hemodynamics; kidney clearance; kidney ischemia; kidney perfusion; male; nephrectomy; nonhuman; plasma osmolality; urine osmolality; urine volume